The Role of Audit Report Lag in Mediating the Effect of Auditor Switching and Financial Distress on Financial Statement Fraud - Emma Rani Nuristya; Dwi Ratmono (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2022)
This paper examines the effect of auditor switching and financial distress on financial statement fraud with audit report lag as the intervening variable. This research used 26 fraud companies and 45 non-fraud companies listed by Indonesia Stock Exchange that break the article VIII.G.7 and IX.E.2 issued by Financial Services Authority in 2020. This quantitative research used Partial Least Square (PLS) with WarpPLS 7.0 tools. We conclude that financial distress and audit report lag directly affect Financial Statement fraud. It also shows that audit report lag partially mediates the relationship between financial distress and financial statement fraud. The results of this study also imply that investors should understand the elements that might cause audit report lag and financial statement fraud, so that they can forecast the impact on possible profits or losses if they invest in a firm.